2002
DOI: 10.1136/thorax.57.2.120
|View full text |Cite
|
Sign up to set email alerts
|

In search of childhood asthma: questionnaire, tests of bronchial hyperresponsiveness, and clinical evaluation

Abstract: Background:The definition or diagnosis of asthma is a challenge for both clinicians and epidemiologists. Symptom history is usually supplemented with tests of bronchial hyperresponsiveness (BHR) in spite of their uncertainty in improving diagnostic accuracy. Methods: To assess the interrelationship between respiratory symptoms, BHR, and clinical diagnosis of asthma, the respiratory symptoms of 1633 schoolchildren were screened using a questionnaire (response rate 81.2%) and a clinical study was conducted in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
97
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(100 citation statements)
references
References 27 publications
2
97
0
1
Order By: Relevance
“…Childhood asthma defined by the parent would have included nonasthmatic wheeze. We and others have found that parent-defined childhood asthma compares well with the definition including bronchial hyperresponsiveness, 42,43 and a looser definition would shift estimates toward the null. 44 The use of ''doctor-diagnosed asthma'' may result in underdiagnosis.…”
Section: Discussionmentioning
confidence: 64%
“…Childhood asthma defined by the parent would have included nonasthmatic wheeze. We and others have found that parent-defined childhood asthma compares well with the definition including bronchial hyperresponsiveness, 42,43 and a looser definition would shift estimates toward the null. 44 The use of ''doctor-diagnosed asthma'' may result in underdiagnosis.…”
Section: Discussionmentioning
confidence: 64%
“…These studies determined that the video questionnaire was a reliable method for determining asthma prevalence [14-16, 24, 25, 31]. Recent research has shown that bronchial hyperresponsiveness (BHR) tests had a low sensitivity (0.35-0.47), whereas using asthma symptoms had high specificity (w0.97) and sensitivity (w0.7) in relation to clinical asthma, which makes them a better tool for asthma epidemiology than BHR [30,[32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…Despite this limitation, we believe that parent-defined childhood asthma is acceptable. Others have found that this definition compares well with one including bronchial hyperresponsiveness, 38,39 and a looser definition will shift estimates toward the null. 40 The use of physician-diagnosed asthma can result in underdiagnosis.…”
Section: Discussionmentioning
confidence: 96%